Certificação ambiental de condomínio horizontal residencial fechado : estudo de viabilidade técnica e econômica ao sistema de certificação LEED-ND - Szilagyi, Carlos Leonardo Sgari (2012)
The growing Brazilian urbanization, coupled with the inadequacy of strategic urban planning, has generated growing social and environmental problems, leading to loss in quality of life. This problem has been worsening over the years with steady population growth and the accompanying factors such as greater accumulation of population in major cities, requiring new ways to view and manage cities. Creating environments with higher quality of life that supply the deficiency in the city meet the locals is essential, and environmental quality is one of the factors that characterize the quality of life. At this point the international certification systems help through constructive guidance procedures appropriate for environmental improvement and consequently improves the quality of life. The city of Passo Fundo - RS does not differ in this feature, which justifies this research, which aims to identify the current process of architectural design and urban planning through an object of study, recommend procedures to fit the system of certification Leadership in Energy and Environmental Design - Neighborhood Development (LEED-ND), estimating the cost of implementation and evaluate the acceptance of real estate agents and entrepreneurs. We adopted a horizontal condominium residential closed as a case study, obtained with a local entrepreneur, who provided data on the design and implementation of the joint owner. The methods used involve in situ surveys, photographs of the site and surroundings, interviews, research in books, magazines and journals to assess the project system deployed in the object under study. Also studied were the following LEED-ND system and its ability to be deployed in the object under study, considering the legal, environmental, cultural and cost estimate. At study end some system procedures were recommended for the adequacy of the condominium certification system, ensuring the minimum score for final certification. The results demonstrate a difference in the current project and the concerns launched by the certification system, showing the need for new ways of designing for certification. They also demonstrate a high initial cost compared to the current budget to adapt to the enterprise system. Finally, there is the research assessment on the system design, system implementation cost of LEED-ND and the opinions of real estate agents and entrepreneurs, showing the possibility of adapting a condominium ever built an international certification system as LEED-ND.